A comparison of postoperative pain and duration of hospital stay between Lichtenstein’s repair and laparoscopic repair of inguinal hernia - Suresh, Geethu; George, Robinson; Balakrishnan, Aravind; Mathew, James (International Surgery Journal, 2025)
Background: This comparative study is to focus on advantage and disadvantage of two types of procedures: open and laparoscopic hernioplasty regarding postoperative pain and duration of hospital stay. Even if similar studies has been conducted outside of Kerala, there is no statistics available from a tertiary care centre in Kerala. In order to promote a more efficient repair approach, I aim to conduct this research to assess the outcomes of both open and laparoscopic repairs and determine whether the minimally invasive repair is superior to open in our setup. The study compares the length of hospital stay and postoperative pain among Lichtenstein's open hernioplasty and laparoscopic hernioplasty. Methods: The 32 patients with unilateral inguinal hernias underwent laparoscopic or Lichtenstein's tension-free repair from November 2022 to March 2024 at the Pushpagiri institute of medical sciences in Tiruvalla. This research was a longitudinal observational study. Results: The comparison of post-operative pain among different groups on various post-operative days on day 2, day 7, day 30 and day 180 revealed a median pain score of 4.5 on day 2, decreasing to 1.5 on day 7, and reaching zero on day 30 as well as day 180. For Lichtenstein's repair, the average duration of hospitalization was 2.5 days and for laparoscopic repair, it was 2 days. Conclusions: Laparoscopic repair was found better in terms of less postoperative pain but no discernible variation among the two groups when duration of hospital stay is concerned.